Dekonstruksi Representasi Perempuan dari Sudut Pandang Sutradara Perempuan dalam Film YUNI - Yassar Hasan; Roro Retno Wulan; Iis Kurnia Nurhayati (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
The emergence of female directors in the Indonesian film industry is expected to be able to represent female characters in films based on the perspective of women themselves. However, in the film YUNI by female director Kamila Andini, a scene was found showing the female lead wearing revealing clothing. This is identical to the concept of the male gaze which makes women the object of the gaze and positions women only as complementary objects or inferior groups. Therefore, the author wants to look more deeply at how women are represented in the film using Sara Mills' critical discourse analysis which goes through the stages of analyzing the subject-object position and the audience position. Based on the results of the analysis, Kamila Andini is in the position of a woman who criticizes the issues experienced by women in a unique way, and deconstructs the old representation of women who are considered an inferior group. Meanwhile, to see the public's perception of the image of women, further research is needed that discusses the perception of Indonesian society towards the image or impression of Indonesian women today.